An in vitro study on the anti-microbial property of santan (ixora coccinea) against oral pathogens - Macapagal, Tanya P.
Oral healthcare is commonly neglected by people. Most indigent Filipinos resort to the more affordable herbal medicine and "arbularyos" due to the high cost of medication. This may also be due to less severe symptoms of disease conditions in the oral cavity. In order to address this problem, several studies have been performed on some Philippine plants to discover alternative forms of drugs and solutions. Santan-pula (Ixora coccinea) is a plant widely available in the country with various reported pharmacological uses. It has been stated that the diluted tincture of santan roots could be used for mouthwash and gargles for sore throat (Quisumbing 1978). This study aimed to determine the anti-microbial property of santan {Ixora coccinea) against oral pathogens, specifically S. mutans, C. albican and S. pyogenes. From several concentrations of the diluted tincture of santan roots in a trial test, those of 55%, 60% and 65% were chosen for the final experiment For each concentration, fifteen (15) samples of each microorganism was tested along with 95% ethanol (positive control) and distilled water (negative control). The zone of inhibition produced by each concentration was measured and compared. The p value at 0.05 with 95% confidence showed that as the concentration of the diluted tincture of santan roots increased, the zone of inhibition observed also increased. Zones of inhibition from the diluted tincture of santan roots was observed in S. mutans and C. albicans only. There was no zone of inhibition observed in S. pyogenes. The values of the zones of inhibition increased as the concentration of the diluted tincture increased. The most significant values yielded from the zones of inhibition were seen with the 65% concentration. Therefore, the diluted tincture of santan roots has anti-microbial properties against the oral pathogens S. mutans and C. albicans.